A Case of Refractory Idiopathic Tumoral Calcinosis Cutis - S. Siddiqui; G. Ahmed; H. Qaisar; Z. Wahid; H. Talat (Nepal Journal of Dermatology, Venereology & Leprology)
A case of idiopathic tumoral calcinosis cutis in a normocalcemic patient. The lesions were localized to multiple large and small joints throughout the body and confirmed on biopsy. The lesions are refractory to intralesional steroids, aluminum hydroxide and diltiazem after 5 months. The patient is being considered for surgical intervention for large lesions while he will be further tried on dialitiazem for the smaller ones.